The Influence of MTHFR Polymorphism on Gray Matter Volume in Patients With Amnestic Mild Cognitive Impairment - You, Mengzhe; Zhou, Xia; Yin, Wenwen; Wan, Ke; Zhang, Wei; Li, Chenchen; Li, Mingxu; Zhu, Wenhao; Zhu, Xiaoqun; Sun, Zhongwu (Frontiers in Neuroscience, 2021)
Methylenetetrahydrofolate reductase (MTHFR) gene is independently linked to the pathogenesis of Alzheimer’s disease (AD). Amnestic mild cognitive impairment (aMCI) is the early stage of dementia and involves a high risk of converting into AD. Although the effects of Apolipoprotein E (APOE) gene on structural alterations in aMCI have been widely investigated, the effects of MTHFR C677T and MTHFR × APOE interactions on gray matter atrophy in aMCI remain largely unknown. Here, 60 aMCI patients and 30 healthy controls were enrolled in our studies, and voxel-based morphometry (VBM) analysis was performed to inspect the effects of diagnosis, different genotypes and their interactions on gray matter atrophy. The results showed that aMCI patients had significant gray matter atrophy on the bilateral hippocampus, right parahippocampal gyrus, and left supper temporal gyrus compared to healthy controls. Besides, APOE ε4 carriers in aMCI group presented a significant gray matter volume reduction on the right hippocampus in comparison to APOE ε4 non-carriers. Significant interaction effect of diagnosis x MTHFR C677T genotype was found on the right precuneus in healthy controls and aMCI patients without APOE ε4 carriers. Our findings may provide new evidence to support genetic effects of MTHFR C677T on brain structural alternation in patients with aMCI.